ASEAN’s Free Mobility of Professional Labor: Benefits and Challenges for Cambodia - Sao Chantola; Ka Mathul (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
ASEAN’s flow of professionals has been carried out since 2015; understanding the outcomes regarding the participation of Cambodia has been observed. Thus, this study used a qualitative approach with experts in international relations, the labour market, and economics. The participants were selected through purposeful and snowballing techniques; in-depth semi-structured interviews were employed, each taking 30-45 minutes. The researchers recorded, coded, and analyzed all interview responses via thematic analysis. The research findings highlighted the opportunities for Cambodia, such as gaining a larger labour market with higher wages and helping skilled workers be recognized across ASEAN. However, Cambodia faced challenges due to the shortage of skilled workers and the mismatch between the local workforce's skills and the labour market's demands. The research recommended that ASEAN should enhance the Mutual Recognition Arrangements and expand more professions, for these days, it covers only a few fields, such as engineering, architecture, and healthcare, and the government should widely spread the ASEAN free of skilled labour agreement to the students so that they can understand and be prepared to compete for job opportunities; Cambodia should improve its quality of education, students should study majors that match the labour market needs, and local jobs should be further created by attracting local and international investors to decrease brain-drain.